Penataan Koridor Jalan Jenderal Sudirman Perkotaan Toboali Kabupaten Bangka Selatan Dilihat Dari Elemen Rancang Kota - Zulphiniar Priyandoko; Adhi Hermawan; Mugi Taufik (Program Studi Perencanaan Wilayah dan Kota Universitas Pasundan, 2015)
Research conducted in the study area is in the form of road corridor which has a length of 7 km that have concerns about elements of urban design, supported with analysis and guidance on eight elements of urban design that consists of Land use, Forms and Procedures Mass Building, Circulation and parking, Tata Information, Support Activity, Pedestrian Line, Green Line Road and Historic Buildings. Jalan Sudirman corridor is the only center of economic growth in South Bangka Regency. In general road corridor sudirman there are several activities such as housing, offices, government, trade, and services. Corridor development Jalan Sudirman currently not offset the premium elements of good urban design. The results of this study is that the growth of the road corridor is very rapid sudirman general should be supported by a particular arrangement of the arrangement of urban design elements, thus creating sudirman general road corridor to improve environmental quality. Recommendations from this study is to perform layout directives of the eight elements of urban design that consists of Land use, shape and mass Tata Building, Circulation and Parking, System Information, Support Activity, Pedestrian Line, Green Line Road and Historic Buildings.